2015
DOI: 10.14327/iscm.9.17
|View full text |Cite
|
Sign up to set email alerts
|

<b>An Ant Colony Optimization Method for Fuzzy Vehicle Routing Problem </b>

Abstract: This paper deals with the vehicle routing problem involved with fuzzy/imprecise vehicle travel times and customer service times, these fuzzy/imprecise times are represented as fuzzy numbers and interpreted as possibility distributions. According to the same consideration as the stochastic programming with recourse, we treate the influence of the fuzziness of travel times and service times as recourse cost. and solve the fuzzy vehicle routing problem through twostage decisions. As the result, a two-stage possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…While Qu et al [11] have clearly showed that neither the algorithm nor the common method can provide drivers with a satisfactory solution for wayfinding in a complex road network of the city on the basis of analysing the advantages and disadvantages of the shortest path algorithm and the problem solving based on knowledge method. Besides, Dong et al [12] used an ant colony optimization method for fuzzy vehicle routing problem, and Abraham et al [13] found the alternative routes in road networks with independent cost function. Also, Arunadevi et al [14] selected route to a given destination on an actual map under a static environment, with a parallel genetic algorithm (PGA) implemented using high performance cluster.…”
Section: Cpu Memory Among Them Through Comparison Experiments Usingmentioning
confidence: 99%
“…While Qu et al [11] have clearly showed that neither the algorithm nor the common method can provide drivers with a satisfactory solution for wayfinding in a complex road network of the city on the basis of analysing the advantages and disadvantages of the shortest path algorithm and the problem solving based on knowledge method. Besides, Dong et al [12] used an ant colony optimization method for fuzzy vehicle routing problem, and Abraham et al [13] found the alternative routes in road networks with independent cost function. Also, Arunadevi et al [14] selected route to a given destination on an actual map under a static environment, with a parallel genetic algorithm (PGA) implemented using high performance cluster.…”
Section: Cpu Memory Among Them Through Comparison Experiments Usingmentioning
confidence: 99%